Age and Individual Differences in the Intellectual Development of Elementary Schoolchildren when Solving SPM Tasks - Vucicevic B. (Moscow State University of Psychology and Education, 2022)
In the study we test the possibility to use the last known classification of wrong responses on the Standard Progressive Matrices for a differentiated assessment of the development of intellectual abilities in primary schoolchildren. The total of 160 pupils enrolled in the 1st (N=80, age 6,7-8,1, M=7,3) and the 3rd (N=80, age 8,8-10,2, M=9,3) classes from two schools in Moscow participated in the study. Our results showed that there are age-related differences in the typical type of wrong responses those two groups make while solving SPM (p<.01), as well as individual or ability-related differences within those age groups (p<.05). This study emphasizes the importance of considering the qualitative peculiarities of the children's thinking processes at different age when analyzing wrong responses on SPM, and the value of applying this approach both in research and psychological practice. The advantages and disadvantages of the used classification of wrong responses are discussed. Finally, since this type of research is being conducted in Russia for the first time, our results are compared with the results obtained in foreign studies.